Immunoexpression of TGF-b in giant cell tumour, central and peripheral giant cell lesions - Abdul Jabbar, Omar; Mustafa Al-Ahmad, Basma Ezzat; Faisal, Ghasak Ghazi (2015)
Aim and purpose: To investigate the difference in biological behavior between Giant Cell Lesion in oral cavity with Giant Cells tumors in long bones by using transforming growth factor beta (IHC) marker. Materials and method: Total of 40 cases of giant cell lesions (C.G.C.G., P.G.C.G. and G.C.T) were included in this study. 17 cases were of G.C.T, 14 of C.G.C.G. and 9 cases were of P.G.C.G. Immunohistochemical staining technique by TGF-b marker was conducted upon these cases showing positive expression in both multinucleated giant cells (MGC) and mononucleated stromal cells (MC) which are considered to be the main histopathological constituent of giant cell lesions.Results: The PGCL showed lightly higher expression of TGF B1 in (MC) than CGCL and GCT but with a non-significant difference value. In comparison of PGCL and CGCL with GCT, they showed higher expression of TGF-b in MGC (p < 0.05). Summary and conclusions: Our results suggest that, in CGCL and PCGL the TGF-b may be important for osteoclastogenesis and bone resorption.